2022
DOI: 10.3390/su14042208
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Recent Trends in Global Sustainable Development Goal 6 Research: Scientometric, Text Mining and an Improved Framework for Future Research

Abstract: The fulfilment of Sustainable Development Goal (SDG) 6, concerning water and sanitation, is critical in itself and also conditional for the other 16 SDGs being met. The purpose of this study was to understand the scientific research trajectories, spatiotemporal development, scientific collaboration, ongoing research themes, and gaps related to SDG 6. We propose a coupling of bibliometric and text mining methods in this work, to statistically portray the impact of water research on the accomplishment of SDG 6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Research themes and gaps, specifically in SDG 6, have been identified using cooperation networks, theme networks, and cluster analysis. There now exists a conceptual framework of SDG 6 and a classification of the relationships between the environment, economy, and society (Roy et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research themes and gaps, specifically in SDG 6, have been identified using cooperation networks, theme networks, and cluster analysis. There now exists a conceptual framework of SDG 6 and a classification of the relationships between the environment, economy, and society (Roy et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research themes and gaps, specifically in SDG 6, have been identified using cooperation networks, theme networks, and cluster analysis. There now exists a conceptual framework of SDG 6 and a classification of the relationships between the environment, economy, and society (Roy et al, 2022). Polychronopoulos et al (2021) used latent Dirichlet allocation (LDA) topic modeling analysis to obtain insights into entrepreneurs' engagement in SDGs.…”
Section: Text Mining Analysismentioning
confidence: 99%
“…Jang (2021) reviewed the academic papers which are published by Springer to specify policy issues related to the education gap using text mining approach. Roy et al (2022) presented the recent trends in SDG 6 (clean water and sanitation) for six years. They used bibliometric analysis based on text mining to support SDG 6.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study focuses on Sustainable Development Goals SDG 6 with target 6.5.1, implementing IWRM at all levels and transboundary water cooperation (TWC) [15,16]. IWRM gained significance during the Rio de Janeiro Summit and Dublin Conference in 1992.…”
Section: Introductionmentioning
confidence: 99%